THE IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARD (SAP) NO. 5 ON INVENTORY ACCOUNTING: A CASE STUDY OF BATU BARA REGENCY - Ignacia Cecilia Rumapea; Yesika Situmorang; Iskandar Muda (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study is entitled Application of Government Accounting Standard (SAP) Number 5 on Inventory Accounting. A Case Study of Batu Bara Regency. This study examines the implementation of Govern ment Accounting Standards (SAP) No. 5 concerning inventory account ing in the Batu Bara Regency Government for the 2021 fiscal year. The data analyzed were derived from the 2021 Local Government Financi al Statements (LKPD) and the Audit Report issued by the Audit Board of the Republic of Indonesia (BPK RI). The focus of this research lies on four dimensions of inventory accounting: recognition, measureme nt, presentation, and disclosure. The findings reveal that Batu Bara Regency has, in principle, complied with SAP No. 5 in terms of policies and reporting practices. However, the audit results highlight several weaknesses in internal control, such as incomplete stock opname proce dures, expired medicines still recorded as inventories, and limited valu ation documentation for donated items. The study concludes that while formal compliance with SAP No. 5 has been achieved, operational imp rovements are necessary to ensure data reliability and transparency in financial reporting.